THE EFFECT OF COLOR SCHEME ON PURCHASE INTENTION WITH ATTITUDE TOWARDS WEBSITE AS MEDIATION VARIABLE (STUDY CASE ON LAZADA.CO.ID IN MALANG) - ANDIKA, INNO KARSA (Jurnal Ilmiah Mahasiswa FEB, 2018)
The purpose of this research is to analyze the effect of the color scheme against the intention to buy with the attitude to the website as a mediator on the website Lazada.co.id in Malang. The sample in this research is in the area of site customers Lazada Malang. This research is explanatory research that explains the causal relationships among variables through hypothesis testing. Data collection techniques in the study using questionnaire and the study of the literature. This research using a sample to 100 respondents in Malang Lazada.co.id visitors. Samples were taken using a purposive sampling technique. The test instrument used for testing the validity of a test is a research instrument, test the reliability, and the classical assumptions of the test. Methods of analysis used is the analysis of model line and hypothesis testing is done using SPSS t test with 21. The results of this study indicate that by using the t test concluded that each color scheme effect significant direct attitude towards websites. Therefore, the Color scheme also has a significant effect and directly against the intention to buy. Attitude Toward significant influential website directly against the intention to buy. In addition, the attitude towards the web site has a positive effect as a mediator between the atmosphere of the online store and purchase intent in the study Lazada.co.id.Â Key Word: Color scheme, Attitude toward website, Purchase Intention